Who is a Lithuanian? In Search of Władysław Mickiewicz’s Motherland - Budrys, Eduardas (Bibliotheca Lituana, 2019)
Władysław Mickiewicz (1838–1926) was one of most active members of the Polish-Lithuanian diaspora: biographer, journalist, librarian, translator, political, social activist, and prolific publicist. Despite all this, he was mainly known as a son and a follower of his father, the great poet Adam Mickiewicz. The lives of these two men intertwined in many ways: both of their youth years were marked by great rebellions, and both had missed them, both having spent most of their adult lives in Paris, writing and dreaming about their motherland. However, while for Adam the motherland was the land of his childhood and youth, for Władysław, it was not that easy to define. For him, Lithuania, Poland, and his great Father had formed a certain ideal – an ideal to live for. Władysław Mickiewicz was a servant of this ideal all his life, constantly pre-serving, popularizing, and sometimes interpreting it – the legacy of his father. These ideals of an eternal Union between Poland and Lithuania, of an archaic Lithuanian Arcadia somewhere in a secluded part of the world, looked so natural in the Romantic days of the poet. It had grown less and less clear at the second part of the 19th century, and especially during the turbulent years of the First World War and the beginning of the interbellum, which brought such a sharp division between Polish and Lithuanian identities, making old ideals appear strange and antiquated. Yet despite this, Władysław Mickiewicz never renounced them. This article explores his life, writings, and the interpretations of the works of his father with the hope of finding his true motherland.
Keywords: Władysław Mickiewicz; identity; Lithuanian identity; Adam Mickiewicz; Adam Mickiewicz Museum in Paris; 19th c. émigrés in Paris